Gambaran Kadar Hemoglobin pada Calon pendonor Usia lebih Dari 46 Tahun di UDD PMI Kabupaten Jepara - Luthfia, Alya; Wikandari, Ririh Jatmi; Widodo, Widodo (Poltekkes Kemenkes Semarang, 2024)
Blood donation is the process of taking a portion of blood from a healthy person then giving it to the person who needs blood. Hemoglobin level examination is one of the donor selection checks to find out whether someone is successful or not to donate blood. A person can donate blood if the hemoglobin level shows a result of 12.5 g / dL – 17 g / dL. A person's hemoglobin level can be influenced by age, because as we get older many organ functions that do not work optimally so that they experience a decrease in Hb levels. The purpose of this study was to measure hemoglobin levels in prospective donors aged more than 46 years at UDD PMI Jepara Regency. This type of research uses a quantitative approach with a cross-sectional descriptive study research model taken from the SIMDONDAR database. The population in this study is all potential donors at UDD PMI Jepara Regency in December 2023-January 2024. The data obtained were analyzed univariately. Based on the results of the study, it was found that the majority of prospective donors showed normal hemoglobin levels as many as 480 prospective donors (94.86%), and more prospective donors who had blood type O (+) as many as 187 prospective donors (36.96%), most prospective donors were male as many as 342 prospective donors (67.59%), and the majority of prospective donors were declared to have passed the donor selection as many as 480 prospective donors (94.86%). The impact of the research results obtained by UDD PMI Jepara Regency is that officers are aware of the importance of socializing to the community how important it is to maintain hemoglobin levels before donating blood and recruiting donors from various ages of prospective donors in the Jepara Regency area.